2010
DOI: 10.1021/ja108437n
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Reversible Handedness Inversion in Self-Organized Helical Superstructures

Abstract: We report here a fast-photon-mode reversible handedness inversion of a self-organized helical superstructure (i.e., a cholesteric liquid crystal phase) using photoisomerizable chiral cyclic dopants. The two light-driven cyclic azobenzenophanes with axial chirality show photochemically reversible trans to cis isomerization in solution without undergoing thermal or photoinduced racemization. As chiral inducing agents, they exhibit good solubility, high helical twisting power, and a large change in helical twisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 52 publications
0
108
0
2
Order By: Relevance
“…Some binaphthyl-derived azobenzene compounds 21-24 (Fig. 5.16) following this principle have been reported [77][78][79][80].…”
Section: Handedness Inversion In Azobenzene-doped Clcs In 2002 Ruslimentioning
confidence: 94%
See 1 more Smart Citation
“…Some binaphthyl-derived azobenzene compounds 21-24 (Fig. 5.16) following this principle have been reported [77][78][79][80].…”
Section: Handedness Inversion In Azobenzene-doped Clcs In 2002 Ruslimentioning
confidence: 94%
“…For example, Li et al recently reported a fast photon mode reversible handedness inversion of a self-organized helical superstructure, that is, the cholesteric LC phase, using chiral cyclic azobenzene compound (R)-22 and (R)-23 [80]. These two compounds show photochemically reversible trans to cis isomerization in solution without undergoing thermal or photo-induced racemization.…”
Section: Handedness Inversion In Azobenzene-doped Clcs In 2002 Ruslimentioning
confidence: 99%
“…In the past decade, a number of light responsive chiral dopants which can change their HTP either upon isomerization or helical inversion have been used to tune the position of a cholesteric reflection notch over a wide range. [116][117][118] A light responsive system which can change its reflection bandwidth based on the intensities of light would be very attractive. First steps for such a responsive system in the visible and infrared regions have been taken by White et al using a chiral azobenzene photoisomer doped in a Ch-LC cell.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%
“…The optical properties of the entire H-PDLC structure can be effectively altered when one externally changes the orientation of LC molecules inside the droplets. 8,9 In this regard, electrical and optical [10][11][12][13][14][15][16][17][18][19] approaches have been extensively exploited to reorient the LC molecules. However, these two manipulation methods have their respective limitations.…”
Section: Introductionmentioning
confidence: 99%